2007
DOI: 10.1016/j.scienta.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different vigour cherry rootstocks on leaves and shoots mineral composition

Abstract: In this study, the field performance of Adara, CAB 6P, Gisela 5, MaxMa 14, Saint Lucie GF 64 (SL 64), Saint Lucie GF 405 (SL 405), and Tabel-Edabriz rootstocks, grafted with two sweet cherry cultivars ('Stark Hardy Giant' and 'Van', Prunus avium L.), were compared after seven years of planting on a calcareous clay-loam soil. The leaf and shoot mineral elements analysed were N, P, K, Ca, Mg, Fe, Mn, Zn, Na and Cu. In the case of both cultivars, tree vigour and cumulative yield were highest on Adara, whereas yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 23 publications
(40 reference statements)
4
47
1
5
Order By: Relevance
“…Em ameixeira, RATO et al (2008) observaram que o tipo de solo influenciou na absorção de nutrientes os porta-enxertos (GF8-1 e GF10-2) e modificou o teor de P e Mg nos frutos. Diferentes teores de nutrientes foram verificados em folhas de cerejeira (Prunus avium L.) quando utilizado diferentes portaenxertos em trabalho realizado por JIMÉNEZ et al (2007).…”
Section: Resultsunclassified
“…Em ameixeira, RATO et al (2008) observaram que o tipo de solo influenciou na absorção de nutrientes os porta-enxertos (GF8-1 e GF10-2) e modificou o teor de P e Mg nos frutos. Diferentes teores de nutrientes foram verificados em folhas de cerejeira (Prunus avium L.) quando utilizado diferentes portaenxertos em trabalho realizado por JIMÉNEZ et al (2007).…”
Section: Resultsunclassified
“…Other authors also reported slight Zn insufficiency in cherry orchards on heavy and calcareous soils (Moreno et al 1996(Moreno et al , 2001Jiménez et al 2007). Tisdale and Nelson (1966) reported a very high Zn insufficiency on an acidic soil, indicating that the inhibition of Zn uptake was not due to soil alkalinity.…”
Section: Dop and σDop Indexesmentioning
confidence: 88%
“…Germresdorfer, had the lowest capacity to accumulate micronutrients. Jiménez et al (2007) and Stochl et al (2008) also reported cultivar differences in leaf micronutrients level.…”
Section: Leaf Nutrient Composition At 60 Dafbmentioning
confidence: 90%
See 1 more Smart Citation
“…The rootstock also modifies the concentration of nutrients in leaves and stems. For example, low-vigor cherry rootstocks are more sensitive under limiting soil conditions (Jiménez et al, 2007). Also, depending on the rootstock and the variety used, rootstocks with more TSCA have lower production efficiency (Zarrouk et al, 2005).…”
Section: Vigor Controlmentioning
confidence: 99%